An Analysis of Interreligious Tolerance and Its Determinants in Preserving Social Unity and Harmony in Indonesia - Octaviana Azizah; Rukhaini Fitri Rahmawati (STKIP Taman Siswa Bima, 2025)
The challenges Indonesia faces regarding religious pluralism have become a significant and prevalent issue. Indonesia's religious diversity is often prone to conflict, especially due to differences in teachings and practices among followers of different religions. Therefore, it is important to understand and practice tolerance as one of the keys to maintaining unity and social harmony in Indonesia. This research aims to explore the forms of tolerance and the factors that influence the level of tolerance in Indonesian society. This research can identify factors that hinder or support tolerance in society, be able to increase public awareness about the importance of tolerance between religious communities and to instill the values of tolerance and empathy for differences that occur in society. This research uses the Systematic Literature Review method, which allows the review of various literatures related to this topic. The selection of articles for this study was done by searching for articles that met the inclusion and exclusion criteria using the Google Scholar database with keywords such as “Religious Tolerance”, “Religious Pluralism”, and “Interfaith Interaction”. This research examined 13 relevant scientific publications published in the last five years (2020-2024). The results of this study reveal three forms of tolerance between religious communities, namely: Tolerance in social interactions, religious practices, and cultural activities. In addition, the factors that influence the tolerance process include the influence of religious leaders and public awareness of the importance of harmonious coexistence.